2017
DOI: 10.1371/journal.pone.0175846
|View full text |Cite|
|
Sign up to set email alerts
|

New function of aldoxime dehydratase: Redox catalysis and the formation of an expected product

Abstract: In general, hemoproteins are capable of catalyzing redox reactions. Aldoxime dehydratase (OxdA), which is a unique heme-containing enzyme, catalyzes the dehydration of aldoximes to the corresponding nitriles. Its reaction is a rare example of heme directly activating an organic substrate, unlike the utilization of H2O2 or O2 as a mediator of catalysis by other heme-containing enzymes. While it is unknown whether OxdA catalyzes redox reactions or not, we here for the first time detected catalase activity (which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…158 Furthermore, the versatile OxdA also functions as catalase, peroxidase, and peroxygenase, revealing its catalytic promiscuity. 169…”
Section: Nitrile Biosynthesis In Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…158 Furthermore, the versatile OxdA also functions as catalase, peroxidase, and peroxygenase, revealing its catalytic promiscuity. 169…”
Section: Nitrile Biosynthesis In Microorganismsmentioning
confidence: 99%
“…158 Furthermore, the versatile OxdA also functions as catalase, peroxidase, and peroxygenase, revealing its catalytic promiscuity. 169 Six new bacterial aldoxime dehydratases were discovered recently by using 3DM system (a soware suite for protein superfamily analysis) based on the well-studied OxdB, namely OxdVP from Variovorax paradoxus, OxdHsp from Hydrogenophaga sp. RAC07, OxdPsp from Pseudomonas sp.…”
Section: Aldoxime Dehydratasementioning
confidence: 99%
“…The non-natural DFSM-facilitated P450-H 2 O 2 system described above mainly catalyzes various per-oxygenation reactions, including epoxidation, hydroxylation, and sulfoxidation [66,[92][93][94][95]. Interestingly, the oxidation of guaiacol, a classical substrate of peroxidases [141][142][143][144], catalyzed by the DFSM-facilitated P450BM3-H 2 O 2 system yielded demethylated catechol as a major product, suggesting it mainly functioned as a peroxygenase but not as a peroxidase [94]. After carefully analyzing the catalytic mechanism of the potential competitive oxidation pathways in the DFSM-facilitated P450BM3-H 2 O 2 system, Ma et al hypothesized that mutation of redox-sensitive residues may enable switching of peroxygenase activity to peroxidase activity [145].…”
Section: Switching Peroxidase Activity Of the Dfsm-facilitated P450 P...mentioning
confidence: 99%
“…On the basis of the established mechanistic understanding of catalytic H 2 O 2 activation in natural peroxidases and peroxygenases, our group has recently used a modified fatty acid hydroxylase protein from Bacillus megaterium (P450BM3) to construct an artificial P450-H 2 O 2 system by installing a rationally designed dual-functional small molecule (DFSM) as a built-in base to assist with H 2 O 2 activation (Figure A). The system efficiently catalyzed various peroxygenation reactions, including epoxidations, sulfoxidations, and hydroxylations (Figure B). , However, catalytic guaiacol oxidation with this system generated demethylated catechol as the major product . Guaiacol is a classical substrate of peroxidases, so this unusual result suggested that the DFSM-facilitated P450BM3-H 2 O 2 system mainly functioned as a peroxygenase but not as a peroxidase (Figure C).…”
mentioning
confidence: 99%